2012
DOI: 10.1111/j.1365-2966.2012.21884.x
|View full text |Cite
|
Sign up to set email alerts
|

The propagation of light pollution in the atmosphere

Abstract: Methods to map artificial night sky brightness and stellar visibility across large territories or their distribution over the entire sky at any site are based on the computation of the propagation of light pollution with Garstang models, a simplified solution of the radiative transfer problem in the atmosphere which allows a fast computation by reducing it to a ray-tracing approach. We present here up-to-date Extended Garstang Models (EGM) which provide a more general numerical solution for the radiative trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 55 publications
2
64
0
Order By: Relevance
“…Model simplifications which were necessary given the computing capabilities in 2001, particularly related to site elevation and atmospheric parameters, could also play a role. The World Atlas will be updated in the coming years based on an improved model29 and improved satellite data30 (due to an overpass time closer to midnight, the new data will not be as dependent upon winter data at high latitudes, when snow cover is common). The SQM data from GLOBE at Night will provide an important independent check of the improved model.…”
Section: Discussionmentioning
confidence: 99%
“…Model simplifications which were necessary given the computing capabilities in 2001, particularly related to site elevation and atmospheric parameters, could also play a role. The World Atlas will be updated in the coming years based on an improved model29 and improved satellite data30 (due to an overpass time closer to midnight, the new data will not be as dependent upon winter data at high latitudes, when snow cover is common). The SQM data from GLOBE at Night will provide an important independent check of the improved model.…”
Section: Discussionmentioning
confidence: 99%
“…The DNB radiance could then be turned into an estimated spectral radiance for the pixel. Spectral radiances would be of greater use in analyses, such as modeling skyglow [16,50], estimating energy consumption [29] and epidemiological studies [18]. Case Study 1 showed that city light is not constant, but changes dynamically over the course of the evening.…”
Section: Resultsmentioning
confidence: 99%
“…years [19][20][21][22][23]. These new developments were made possible thanks to the increasing availability of high-performance computing resources, as well as to the availability of geographical datasets, such as night-time satellite data.…”
Section: Introductionmentioning
confidence: 99%